ANCA associated vasculitis: The journey to complement-targeted therapies. (August 2019) - Quintana, Luis F.; Kronbichler, Andreas; Blasco, Miquel; Zhao, Ming-hui; Jayne, David
Highlights: End stage renal disease by ANCA vasculitis affects 40% of the patients. Major hurdles are the complex balance between treatment toxicity and recurrence. New data indicate that C5 and C5aR are therapeutic targets in ANCA renal vasculitis. The way is open for clinical use of this complement target therapy in the near future. Abstract: ANCA associated vasculitis is a serious, very often recurrent disease that despite the current standard treatment with high-dose glucocorticoids and either cyclophosphamide or rituximab, patients have a nine-fold increased mortality risk in the first year compared with healthy controls, attributed to infections, vasculitis activity, and renal disease. During the last few years, novel findings have suggested that activation of the complement system, in particular the alternative complement system, has a significant role in ANCA associated vasculitis pathogenesis. Detection of several components of this system in the circulation and urine reflects disease activity, and thus may be useful for clinical prognosis and to set up personalised treatments. In fact, some components of the complement system, such as C5a, might be potential targets for therapy. In this Review an update on clinical evidence for the role of complement activation in AAV is provided and subsequently we discuss potential therapeutic strategies that target complement components and open the way for clinical use of this target therapy in the near future.